Regional and sectoral effects of a common monetary policy: Evidence from euro referenda in Denmark and Sweden - Gabriel M. Ahlfeldt; Wolfgang Maennig; Tobias Osterheider (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2009)
This article provides empirical evidence for the (anticipated) net costs and benefits of a common monetary policy that varies across regions depending on the industry mix. The paper is the first to approach the issue of the regional and sectoral effects of a common monetary policy by using empirical spatial models to analyze referenda. Here, the referenda examined are the 2000 and 2003 referenda held in Denmark and Sweden regarding participation in the EMU. We find that voters in regions with a high proportion of interest-sensitive sectors and low international integration tend to oppose participation in a currency union. The opposite is true for non-interest-sensitive sectors with relatively high integration. These findings are in line with the hypothesis of rational voters maximizing utility. Furthermore, perceived net costs are found to increase with distance from the European core and with the age of voters, indicating that a national currency represents an experience good. These results are robust to spatial dependencies and are not driven by broader forms of Euro-skepticism.
Keywords: E52; P16; R12; 330; EMU; Euro; Regional & Sectoral Effects of Monetary Policy; Public Referenda; Denmark; Sweden